Nowe zagrożenia, stare lęki? Hollywoodzkie "kino konspiracyjne" i jego konteksty - Piskorz, Artur (Er(r)go. Teoria - Literatura - Kultura, 2007)
Artur Piskorz New Threats, Old Fears? Contemporary Hollywood 'Conspiracy Films' and Their Contexts Hollywood cinema has always been keen on producing films dealing with various forms of conspiracy. A particularly prolific era begun towards the late 1960s and continued for nearly a decade. Leftist filmmakers (e.g. Alan J.Pakula, Sidney Pollack) made a number of 'conspiracy films' constituting an artistic response to the social and political upheavals of the times (the Pentagon Papers, the Watergate scandal, the Vietnam War, the ITT and Lockheed disclosures, and so on). This cycle of films was to stay with the American filmmakers ever since. Virtually every major political controversy earned itself a conspiracy theory and its filmic representation. Depending on the current 'fashion', the films have tackled diverse subjects ranging from the fear of total control to the fear of the world government to the problem of global terrorism after the 9/11 attacks. With the advance of cheap digital technology as well as the Internet, various individuals have been utilizing their opportunity to make films 'unmasking' global conspiracies and plots. This has become particularly widespread after the events of September 11. The essay inquires into the possibility of establishing any patterns of discourse between the classic productions and the new, emerging ones.